2013
DOI: 10.3171/2013.4.peds12605
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cranioplasty following decompressive craniectomy in the pediatric population

Abstract: Cranioplasty is routinely performed following decompressive craniectomy in both adult and pediatric populations. In adults, this procedure is associated with higher rates of complications than is elective cranial surgery. This study is a review of the literature describing risk factors for complications after cranioplasty surgery in pediatric patients. A systematic search of PubMed, Cochrane, and SCOPUS databases was undertaken. Articles were selected based on their titles and abstracts. Only studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 24 publications
6
68
0
Order By: Relevance
“…Also, time between craniectomy and cranioplasty did not have a significant effect on complication rate. 13 The results came from studies in the pediatric population but were consistent with our study. In contrast to our study, Zhou et al reported that the outcome of a single-stage operation combining VP shunt placement and cranioplasty did not significantly differ from that for two separate operations.…”
supporting
confidence: 80%
“…Also, time between craniectomy and cranioplasty did not have a significant effect on complication rate. 13 The results came from studies in the pediatric population but were consistent with our study. In contrast to our study, Zhou et al reported that the outcome of a single-stage operation combining VP shunt placement and cranioplasty did not significantly differ from that for two separate operations.…”
supporting
confidence: 80%
“…Most surgeons prefer the previously stored cranial bone flap for the initial cranioplasty attempt due to its biocompatibility, perfect shape and possible osteo-inductive effects. However, the autologous graft is no more applicative when a revision cranioplasty is required (15,29). In case of a failed cranioplasty, surgeon faces with giving a decision between far-site autologous grafts, allografts or synthetic implant materials.…”
Section: █ Discussionmentioning
confidence: 99%
“…Bone turnover is relatively higher in pediatric age, thus the spontaneous bone resorption is mostly the leading reason for revisions (29 There is not a consensus on surgical strategy for revision cranioplasty. When indicated, the timing of the surgery also remains a debate especially for patients with infected bone flap and skin.…”
mentioning
confidence: 99%
“…13,32,33 Decompressive craniectomy carries a complication risk of 37%-50%, 5,13,32,79 and patients undergoing a cranioplasty for the repair of a craniectomy defect face an additional 16%-34% complication risk. 3,9,14,23,24,46,57,65,75 One caveat regarding the DECRA trial is that only patients without any significant mass lesions were enrolled. 13 Some studies seem to suggest that a craniectomy may improve outcome when used for the treatment of elevated ICP associated with a mass lesion.…”
mentioning
confidence: 99%